2019
DOI: 10.2495/safe-v9-n1-50-60
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale reinforced concrete slabs: blast effects, damage characterization and numerical modelling

Abstract: This work investigates the response of a blast loaded reinforced slab with different constructive characteristics. This topic has been well covered during the last years, but there are a reduce number of them that presents blast test at realistic scale. Seven different slabs were tested: three at a scaled distance of 0.79 m/kg 1/3 , one at 0.41 m/kg 1/3 and four with 0.20 m/kg 1/3. The three tests with high-scaled distance, used as calibration tests, have been characterized with pressure gauges and acceleromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As can be seen in Figure 10, models reproduce well the result of the field test. Furthermore, data extracted about area of damage are acceptable when compared with those measured in the field with errors up to 15% [17].…”
Section: Figurementioning
confidence: 91%
“…As can be seen in Figure 10, models reproduce well the result of the field test. Furthermore, data extracted about area of damage are acceptable when compared with those measured in the field with errors up to 15% [17].…”
Section: Figurementioning
confidence: 91%
“…They concluded that increase in rise height and front plate thickness can improve the overall response of the panel. Castedo et al [5] performed an experimental and numerical study on slabs reinforced with steel and polypropylene and used non-destructive tests to characterize the damage. Athanasiou et al [6] used LS-DYAN to study the effect of near-field blast on a two-layered reinforced RC slab with different detonation charge.…”
Section: Introductionmentioning
confidence: 99%